Brief meaning toolkit: increasing meaning for the Millennial Generation in the workplace in the era of the New World Order - Effendy, Nurlaila; Dewi, Desak Nyoman Arista Retno (LPPM UNIVERSITAS DIAN NUSWANTORO, 2024)
In the post-pandemic era, current geoeconomic and geopolitical changes will have global, regional, and local impacts. Companies must adapt to rapid changes. This condition causes a person to experience disturbances or even be able to adapt and see opportunities in the new world order in the company. The ability to think reflectively that oneself is crucial, understand life, and determine broader goals for life with meaning is important in responding to situations. The millennial generation dominates the workforce in Indonesia, so millennial employees need to have meaning to support the organization's strategic plan in overcoming difficult situations. This service aims to provide interventions to increase meaning in millennial generation employees. The solution method is to provide an understanding of the meaning and a brief meaning toolkit online for millennial employees based on the Meaning toolkit from Mcquaid & Peggy and developed according to Indonesian Culture. Measurements were carried out by pre-test and post-test with The Work and Meaning Inventory (WAMI) instruments. The intervention results showed increased meaning among participants, although not high, with three sub-toolkits in short sessions and through online media. There is the lowest question, which is related to individual goals and organizational goals. The role of the organization is needed in building meaning in the organization. Based on the initial results of this short intervention, the meaning module can be developed into a more complete sub-toolkit and implemented face-to-face for a longer duration.